PENAFSIRAN, PENALARAN, DAN ARGUMENTASI HUKUM YANG RASIONAL - Tommy Hendra Purwaka (Faculty of Law, Universitas Diponegoro, 2011)
Indonesia applys civil law system which emphasizes on written law. This is why almost ail Indonesian positive laws are written law. Implementation of written laws needs rational legal interpretation, legal reasoning and legal argumentation in order to be able to follow development changes of Indonesian people. Results of legal interpretation, legal reasoning and legal argumentation will explain why certain laws and regulations are applied for a certain fenomena, or considered as applicable laws and regulations for certain development activities, or should be formed as legal base for certain activities. Rational legal interpretation, legal reasoning and legal argumentation should aim at enforcement of legal certainty, justice, and truth. Kata kunci: Penafsiran Hukum; Penalaran Hukum; Argumentasi Hukum